The Relationship between Students' Life Satisfaction and Leisure Attitudes (Research on Students of Physical Education and Sports) (Journal of Pharmaceutical Negative Results, 2023)
This study aimed to evaluate the relationship between life satisfaction and leisure attitudes of students studying at the School of Physical Education and Sports. Another aim of the study is to examine the leisure attitude and life satisfaction levels of students according to the variables of gender, age, class, physical activity participation status and family monthly income. In the research, quantitative research; relational screening method and causal comparison method were applied. The population of the study consisted of Istanbul Gelisim University School of Physical Education and Sports department's students, and the sample (n=426) consisted of volunteer participants. Easy sampling method was preferred as the sampling method. The data were collected by questionnaire technique. Sociodemographic questions including gender, age, class, level of participation in activities and income level variables, Leisure Time Attitude Scale and Life Satisfaction Scale were applied to the participants. The data obtained were transferred to IBMM SPSS24 programme and Mann Whitney U, Kruskal Walls H and Spearman Correlation analysis were applied to determine the relationship levels. Statistical significance level was accepted as p<,050.It was determined that there was no difference in life satisfaction level and leisure attitudes according to the gender of the students. No difference in life satisfaction was detected according to the age and class variables of the students, but there was a significant difference in life satisfaction according to activity participation status and family income level. A significant difference was detected in the perception towards leisure attitudes according to the age, class, activity participation status and family income level variables of the students. Moreover, a weak positive relationship was determined between life satisfaction and leisure time attitude.It was determined that life satisfaction level and leisure time attitudes of male and female students showed similar characteristics. It was determined that the age variable was not a determining variable in the level of life satisfaction, and the attitudes of the participants between the ages of 24-26 were at a better level towards leisure time. It was determined that as the grade level increased, the level of leisure attitude decreased, which was significant, and the grade level was not effective in life satisfaction. It was determined that the life satisfaction and leisure attitudes of the students who regularly participated in recreational and sportive activities were at a better level and statistically significant. It was determined that as the family income level of the students increased, their life satisfaction increased, and the income level variable was a determinant variable in life satisfaction. It was determined that family income level was an important variable in the perception of leisure attitude, and as the income level increased, leisure time attitude was positively affected. It was determined that as the life satisfaction level of the students increased, leisure time attitude also increased and there was a linear relationship between life satisfaction and leisure time attitude.